Bias-point pulsing system for RF power transistors’ characterization - Lopes, Inês Cristina Pereira (2022)
With the exponential evolution of mobile networks, the systems are demanded, not only to work at high power levels and to be more efficient, but also to operate at higher frequencies and with more bandwidth. For that, the scientific community is always trying to obtain the best performance possible for the mobile networks base stations. The efficiency limiting component of these base stations is the RF power amplifier, that is composed by a transistor capable of amplifying the signal that is wanted to transmit. Nowadays, the most used devices are the GaN HEMT (Gallium Nitride High Electron Mobility Transistor), that allow operations with high power density and high bandwidth. However, these devices suffer from several dynamic phenomena that cause the current to collapse and, consequently, the reduction of the power delivery capability. To predict and try to compensate these dynamic behaviours, it is necessary to characterize the transistors in a state where these phenomena are known, which means that isodynamic measurements should be obtained. This work focuses on designing a system that allows to perform pulsed measurements on a transistor and that avoids temperature effects and other dispersive phenomena characteristic of the mentioned technology (known as trapping). For that, two circuits were developed: one for the transistor gate, with a voltage range from −10V to 2V, a maximum current of 2A and a settling time of 500 ns, and another for the transistor drain, with a maximum voltage of 160V, a current of, at least, 15A and a settling time of 4 μs. With this system, it was possible to analyse the impact of the temperature on the measurements, through the study of the pulse width and duty-cycle variation, and it was also possible to study the impact of the trapping, by applying the double pulse technique. As the trapping is a dynamic phenomenon, there are associated time constants that should be known, so it is possible to study the dynamic nature of the devices. Finally, to prove that the system could be used to characterize several devices, GaN HEMT transistors rated for different power values were characterized. In the end, it was possible to obtain their pulsed isodynamic I/V curves, as well as the time constants associated with the trapping effect. With all the obtained results, it was possible to conclude that the system is capable of performing the desired measurements needed to characterize a device, and that the dynamic of the mentioned effects is characteristic of each device, so it should always be carefully analysed.